2022
DOI: 10.3390/cells11203258
|View full text |Cite
|
Sign up to set email alerts
|

An Alzheimer’s Disease Patient-Derived Olfactory Stem Cell Model Identifies Gene Expression Changes Associated with Cognition

Abstract: An early symptom of Alzheimer’s disease (AD) is an impaired sense of smell, for which the molecular basis remains elusive. Here, we generated human olfactory neurosphere-derived (ONS) cells from people with AD and mild cognitive impairment (MCI), and performed global RNA sequencing to determine gene expression changes. ONS cells expressed markers of neuroglial differentiation, providing a unique cellular model to explore changes of early AD-associated pathways. Our transcriptomics data from ONS cells revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…In our case, we used an olfactory proteotranscriptomic-based computational drug-repurposing method to identify drugs that induce a gene expression signature which negatively correlates with early AD phenotype as a strategy for unveiling potential new therapies. First, we compiled the current OT proteomic study as well as other proteomic or transcriptomic studies performed in different primary and secondary olfactory areas (olfactory mucosa, olfactory bulb, entorhinal cortex, hippocampus) in initial stages of AD (11, 14, 22, 33, 34). The OT (Braak I-II) differential dataset was also divided in different lists depending on ALZData parameters (Aβ or Tau correlation in AD murine models, early differentially expressed genes) and on the presence of DEPs in Aβ-plaques, according to previous proteomic evidence obtained by laser-capture microdissection approaches in human AD (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…In our case, we used an olfactory proteotranscriptomic-based computational drug-repurposing method to identify drugs that induce a gene expression signature which negatively correlates with early AD phenotype as a strategy for unveiling potential new therapies. First, we compiled the current OT proteomic study as well as other proteomic or transcriptomic studies performed in different primary and secondary olfactory areas (olfactory mucosa, olfactory bulb, entorhinal cortex, hippocampus) in initial stages of AD (11, 14, 22, 33, 34). The OT (Braak I-II) differential dataset was also divided in different lists depending on ALZData parameters (Aβ or Tau correlation in AD murine models, early differentially expressed genes) and on the presence of DEPs in Aβ-plaques, according to previous proteomic evidence obtained by laser-capture microdissection approaches in human AD (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple groups have prepared/enriched primary neuronal cells and stem cells from the OE via nasal biopsy from living subjects [30][31][32][35][36][37][38][39]57,61,62 . Molecular and cellular analyses of these cells from schizophrenia and related disorders have displayed deficits, indicating pathological alternations in the OE in these disorders [30][31][32][35][36][37][38][39]57,61,62 . Although changes associated with the olfactory system in patients with schizophrenia and related disorders are prominent and reproducibly reported from many groups 1,3,7,14,16,18,20,30,35,39,46,[57][58][59][60]63 , their mechanistic link is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a reduced OB volume in these disorders 16,46,[57][58][59][60] , but the sample size of these studies was relatively small. Multiple groups have prepared/enriched primary neuronal cells and stem cells from the OE via nasal biopsy from living subjects [30][31][32][35][36][37][38][39]57,61,62 . Molecular and cellular analyses of these cells from schizophrenia and related disorders have displayed deficits, indicating pathological alternations in the OE in these disorders [30][31][32][35][36][37][38][39]57,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…These features included the thickness of the left paracentral lobule and sulcus (L.PTs), as well as the expression levels of CTCF, UQCR11, and WDR5B genes. Rantanen et al (2022) analyzed transcriptomic data from olfactory neural sphere (ONS)-derived cells in MCI and AD patients. They discovered a significant difference in the expression of AKAP6, which is associated with cognitive function.…”
Section: Identification Of Shared Candidate Biomarkers Between Ad And...mentioning
confidence: 99%